FIRE SAFETY COMPLIANCE AMONG HOSPITAL BUILDINGS: A CASE STUDY FROM NEPAL-ASIA - Bashyal, Chandramani; Mishra, A.K.; Aithal, P.S. (International Journal of Research -GRANTHAALAYAH, 2022)
Purpose: Hospital building is more sensitive to fire as it has large number of patients who might need assistance during evacuation. The assessment focuses to the Compliance for fire safety by accessing different standards; availability of equipment and systems, exit requirements and awareness among the departmental staffs of Hospitals. Design/Methodology/Approach: The study confined to the 4 hospitals from Bharatpur Metropolitan, Nepal based on judgmental sampling viz; Bharatpur Hospital, BP Koirala Memorial Cancer Hospital, College of Medical Science and Chitwan Medical College building. Literature review was done followed by observation with checklist, questionnaire survey and key informant interview. Findings/Result: The study revealed that the fire safety preparedness was not a priority in the hospitals. All hospital buildings were designed following National building codes. Both private and public Hospitals, practically every one of them uncover a similar degree of readiness. Bharatpur hospital lacked many firefighting equipment such as smoke detector, heat detector, fire alarm and water hose reel. Water sprinkle was missed on all hospitals. Obstruction was found in the escape route. Lacked exit signs and floor indications. Staffs were found aware about the general component of the structure like structure plan, area for exit and assembly points but lacked awareness on emergency procedure. Originality/Value: This research complements the existing building code requirements and fire safety implementation especially for hospital building as Nepal is not having specific provisions for hospitals fire safety. It is assumed to be applicable for policy making in concerned authority & forms basis for further research.